High abundance of drosophilids and low species richness, a reality of composition in a cultivated environment in Pernambuco (Research, Society and Development, 2021)
Drosophilids are organisms that adapt to the most varied environments, natural preserved or anthropized. The impacts caused in natural areas directly interfere in the composition of the different species that colonize this environment. Due to their sensitivity to environmental variations, these small flies have been used as natural bioindicators of environmental changes, while others have great dispersal and colonization power in different ecosystems. Environmental changes can interfere with the abundance of species present in the natural environment, causing the local extinction of some of these species. Among the Brazilian biomes, the Atlantic Forest is the most destroyed by anthropic actions, being, therefore, considered one of the world priorities for the conservation of biodiversity. In order to better understand the effects of this process and characterize the composition of Drosophilidae (Insecta, Diptera) in a devastated Atlantic Forest environment, considered a cultivation area in the Municipality of Nazaré da Mata, Pernambuco, these insects were collected in two seasonal periods distinct (rainy and dry). A total of 5524 individuals were sampled, 3405 in the rainy season and 2119 in the dry season, represented by four (Drosophila, Rhinoleuconphenga, Sacaptodrosophila and Zaprionus) and 16 species of Drosophila, of which the genus Drosophila was more representative, with 13 recognized species. Accounting for both collections, there was a great predominance of three exotic species: Drosophila malerkotliana, D. simulans and Zaprionus indianus, which represent 78% of the total number of individuals. The analysis of richness (Taxa S) was similar between the sampled periods, however, the greatest abundance of individuals was registered in the rainy season. The Simpson (1-D) and Shannon (H) diversity analysis results indicate that there was no significant difference for the seasonal periods regarding the drosophilid fauna.